Plant bio-stimulant: prospective, safe and natural resources - Matthews, Stella; Ali, Asgar; Siddiqui, Yasmeen; Supramaniam, Christina Vimala (Springer, 2022)
The agricultural sector is facing corollary challenges of increasing food production to feed the growing global population and enhance the resources use efficacy, with the least impact on the ecosystem, environment, and human health. In the past few decades, several frontier technologies have been advanced to improve the sustainability of agricultural production systems, through a significant reduction of synthetic agrochemicals. Amongst all, potential and environmentally friendly innovation would be the use of natural substances as plant bio-stimulant that upsurge nutrient uptake for better productivity and also ameliorate the tolerance against several abiotic factors. Moreover, nano-technology is a handy tool for the development of an effective plant bio-stimulant for boosting crop production, assuring sustainability and achieving food security. This review highlights the potential of nano-chitosan, alginate oligosaccharides, nano-silicon, plant extracts, microalgae, agricultural and industrial organic wastes in the development of plant bio-stimulant. Challenges pertaining to nano-formulations and their application in agricultural production are also discussed. Nanoparticles derived from organic and natural elements that are not destructive to the environment and boost sustainable crop cultivation have a great perspective to be developed as an innovative and efficient plant bio-stimulant.